Stylistic and Communicative Functions of Elliptic Sentences in the English Language - Ruzmatova Gulnara Kulmamatovna; Primov Bakhodir Yarashovich (Euro Asian Journal Publishing, 2024)
In the given article elliptical sentences in the English language have been analyzed. The definition of the notion of elliptical sentences given by various linguists, stylistic and communicative functions of elliptical sentences and their grammatical features have been discussed. The role of elliptical sentences in literary works and their peculiarities have been observed
Keywords: ellipsis; elliptical sentences; communicative semantics